2015
DOI: 10.1186/s12943-015-0351-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipid starvation and hypoxia synergistically activate ICAM1 and multiple genes in an Sp1-dependent manner to promote the growth of ovarian cancer

Abstract: BackgroundElucidation of the molecular mechanisms by which cancer cells overcome hypoxia is potentially important for targeted therapy. Complexation of hypoxia-inducible factors (HIFs) with aryl hydrocarbon receptor nuclear translocators can enhance gene expression and initiate cellular responses to hypoxia. However, multiple molecular mechanisms may be required for cancer cells to adapt to diverse microenvironments. We previously demonstrated that a physical interaction between the ubiquitously expressed tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(92 citation statements)
references
References 45 publications
(65 reference statements)
0
92
0
Order By: Relevance
“…It has been shown that hypoxic conditions raise the expression of these transcription factors in nuclear extracts (59), suggesting that the hypoxia-stimulated upregulation of NDRG1 may be mainly mediated by a combined effect of these factors and to a lesser extend by Smad7 and YB-1. A cooperative mechanism, as suggested in the present study, has been shown to promote the regulation of genes necessary for cell adaptation to varying microenvironments such as during starvation and hypoxia (60). Indeed, NDRG1 promoter studies revealed that a SP1 site partially is responsible for the VHL-induced suppression of NDRG1 (61,62).…”
Section: Discussionmentioning
confidence: 84%
“…It has been shown that hypoxic conditions raise the expression of these transcription factors in nuclear extracts (59), suggesting that the hypoxia-stimulated upregulation of NDRG1 may be mainly mediated by a combined effect of these factors and to a lesser extend by Smad7 and YB-1. A cooperative mechanism, as suggested in the present study, has been shown to promote the regulation of genes necessary for cell adaptation to varying microenvironments such as during starvation and hypoxia (60). Indeed, NDRG1 promoter studies revealed that a SP1 site partially is responsible for the VHL-induced suppression of NDRG1 (61,62).…”
Section: Discussionmentioning
confidence: 84%
“…Pimonidazole is a chemical agent that reacts with amino acid residues of proteins in cells exposed to severe reducing (hypoxic) conditions. IHC analysis of A2780 tumors orthotopically (intraperitoneally) implanted into nude mice 74 and OVISE tumors subcutaneously implanted into non-obese diabetic/severe combined immunodeficiency mice 75 using antibodies raised against pimonidazole amino acid adducts demonstrated that ovarian tumor tissues are severely hypoxic. Furthermore, a SKOV-3 tumor model revealed that ovarian cancer cells form spheroids and grow in the peritoneal cavity, and their core was severely hypoxic.…”
Section: Transcriptional Regulation Of Tf and Fvii In Ovarian Cancer mentioning
confidence: 99%
“… 76 These results are consistent with the general concept that solid tumors contain areas of severe hypoxia. 75 …”
Section: Transcriptional Regulation Of Tf and Fvii In Ovarian Cancer mentioning
confidence: 99%
“…Next, we look further into the binding capacity of HIF1α with other cofactors, like Sp1, CBP, p300, and we found that NLGP prevents colocalization of HIF1α with CBP, p300 and Sp1 but not with Sp3, which can competitively target HIF1α and Sp1 binding. Sp1 and Sp3 compete for binding to the HRE region as they share more than 90% sequence homology (39)(40)(41). Consequently, we observed significant less binding of active HIF1α complex with HRE region.…”
Section: Discussionmentioning
confidence: 71%